Differences in breaking behavior of rice leaves under microwave and naturally drying processes - Wang, Meilin; Tang, Zhong; Zhang, Ben; Li, Yu (International Journal of Agricultural and Biological Engineering, 2022)
In order to fight for good farming time or harvest in bad weather, combine harvester will produce more broken leaves when threshing high moisture content rice, which will seriously hinder the grain cleaning effect. In this study, the breaking behavior of rice leaves under different microwave drying time and drying power was studied. Firstly, based on the appearance of freshly rice leaves undergoing microwave drying, the changing property of moisture content, weightlessness rate and temperature rise of rice leaves were tested and analyzed. Secondly, the tensile breaking force of freshly rice leaves under different microwave drying time and drying power was tested and compared with the tensile breaking force of naturally dried rice. Finally, the optimal microwaves parameters of rice leaves after drying which could result in greater breaking force than the natural drying state were obtained. The result showed that microwave drying method will reduce the moisture content of rice leaves and change the microstructure, which would affect the tensile-breaking property of rice leaves. The maximum tensile breaking force of rice leaves appeared at microwave dried power 70 W for 5-8 min and at microwave dried power 210 W for 3-4 min. The tensile breaking property of rice leaves at microwave dried power 350 W for 6-8 min were the weakest, which was lower than that of fresh rice leaves. Therefore, the optimal microwave drying parameters of rice leaves will provide a basis for the application of microwave technology in the threshing process. Keywords: rice harvesting, rice leaves, microwave drying, moisture content, breaking force DOI: 10.25165/j.ijabe.20221501.6400 Citation: Wang M L, Tang Z, Zhang B, Li Y. Differences in breaking behavior of rice leaves under microwave and naturally drying processes. Int J Agric & Biol Eng, 2022; 15(1): 89–100.